2002
DOI: 10.1046/j.1365-2796.2002.01011.x
|View full text |Cite
|
Sign up to set email alerts
|

Carotid artery intima‐media thickness and brachial artery flow‐mediated vasodilation in asymptomatic Japanese male subjects amongst apolipoprotein E phenotypes

Abstract: ). Carotid artery intima-media thickness and brachial artery flowmediated vasodilation in asymptomatic Japanese male subjects amongst apolipoprotein E phenotypes. J Intern Med 2002; 252: 114-120.Background. Epidemiological studies suggest that apolipoprotein E (apoE) polymorphism influences plasma lipoprotein levels and the development of cardiovascular disease. Objective. To clarify the role of apoE polymorphism as a risk factor for early atherosclerosis. Design. Using a high-resolution ultrasound method, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 33 publications
(48 reference statements)
1
29
1
Order By: Relevance
“…In a study done by Haraki T.et al it was observed that by univariate analysis, CCA-IMT was positively correlated with age (r=0.51, p < 0.01), LDL-c/HDL-c ratio (r=0.37, p<0.01), triglycerides (r=0.23, p < 0.05), and negatively correlated with HDL-cholesterol (r=-0.31,p< 0.01). 18 Our findings are very similar to the findings of Haraki et al, 15 excepting for the age. In a study done by Nagasaki T, et al 19 it was observed that CCAIMT change was closely associated with basal levels of total cholesterol (r = 0.472, p= 0.0031), low-density lipoprotein (LDL) cholesterol (r = 0.441, p= 0.0076) and the total/HDL cholesterol ratio (r = 0.435, p= 0.0057) 55 which is similar to the current study.…”
Section: Resultssupporting
confidence: 92%
“…In a study done by Haraki T.et al it was observed that by univariate analysis, CCA-IMT was positively correlated with age (r=0.51, p < 0.01), LDL-c/HDL-c ratio (r=0.37, p<0.01), triglycerides (r=0.23, p < 0.05), and negatively correlated with HDL-cholesterol (r=-0.31,p< 0.01). 18 Our findings are very similar to the findings of Haraki et al, 15 excepting for the age. In a study done by Nagasaki T, et al 19 it was observed that CCAIMT change was closely associated with basal levels of total cholesterol (r = 0.472, p= 0.0031), low-density lipoprotein (LDL) cholesterol (r = 0.441, p= 0.0076) and the total/HDL cholesterol ratio (r = 0.435, p= 0.0057) 55 which is similar to the current study.…”
Section: Resultssupporting
confidence: 92%
“…The majority of studies to date that have examined the relationship between BFMD and anatomical measures of atherosclerosis have tended to focus on men or populations without clinical CVD. Correlations between BFMD and IMT reported by these studies ranged from r = −0.21 to −0.41 [13,[15][16][17], which are of greater magnitude than we observed (r = −0.12). Our findings in women with mild to moderate CAD provide support that the relationship between BFMD and anatomical measures of atherosclerosis holds true in women and among those with CAD, albeit at a lower magnitude than previously reported.…”
Section: Discussioncontrasting
confidence: 65%
“…While QCA and CIMT are associated with prevalent CVD and have strong prognostic value for incident CVD independent of risk profiles [1,3,[6][7][8][9], the diagnostic and prognostic importance of BFMD for CVD is less certain [10]. Although some studies have shown BFMD to be predictive of future coronary events [11,12], only a handful of studies have reported an inverse association between BFMD and CIMT [13][14][15][16][17][18]. The majority of these studies were small, cross-sectional evaluations of men with pre-existing coronary artery disease (CAD) [13,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects were examined in the supine position after 15 minutes of rest in a dark, quiet, air-conditioned room (22)(23)(24). Brachial artery FMD was measured by a trained technician according to the guidelines for the ultrasound assessment 20) .…”
Section: Measurement Of Fmdmentioning
confidence: 99%